LABOR PRODUCTIVITY AND ITS FACTOR ANALYSIS - L.Naranchimeg (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Productivity growth plays a prominent role in the economic and social development of any country. Productivity is an indicator showing how many goods and services are to be produced for the assigned cost. Productivity is improved by managing and organizing business operations effectively, employing scarce resources efficiently and by producing quality products and services that meet market demand and needs. As productivity growth develops, the competitiveness of the country or business entity rises, social wealth is increased and income levels and living standards of the citizens are improved. The experiences of highly developed countries show that productivity plays a role in the leverage of economic growth and developments not only at the country level, but at the level of business entities or even on households and individuals. Thus an accurate estimation of labor resources of the organization by added value needs to be conducted and the resources analyzed by assessing utilization efficiency and influencing factors of labor productivity.